Immune response of broiler chickens supplemented with pediatric cough syrup including thyme extract in drinking water against influenza vaccine - Forough Talazadeh; Mansoor Mayahi (Shahrekord University of Medical Sciences, 2017)
Introduction: This study was conducted to investigate the effects of thyme extract in drinking water on immune response of broiler chickens. Methods: A total of 245-day-old broiler chicks were purchased and 20 chicks were bled for determination maternal antibody and remaining chicks were divided into 5 equal groups. Chickens of group A, B and C received 0.1%, 0.15% and 0.2% of Pediatric Cough Syrup including thyme extract respectively in drinking water for all of the experimental period. Chickens of group D were not received Pediatric Cough Syrup but vaccinated against Influenza disease. Chickens of group E were kept as control group and were not received Pediatric Cough Syrup and Influenza disease vaccine. Chickens of group A, B, C and D were vaccinated with AI-ND killed vaccine (subtype H9N2), subcutaneously in neck back. Blood samples were collected before vaccination as well as on days 14, 28 and 35 after vaccination. Ten chickens of each group were bled randomly and antibody titer against influenza vaccine virus was determined by hemagglutination inhibition (HI) test. Results: The results of the present study showed that Pediatric Cough Syrup including thyme extract at 0.2%, increased the specific antibody response against Influenza vaccine virus compared to all groups. Conclusion: Pediatric Cough Syrup including thyme extract can improve the specific antibody response against Influenza vaccine virus.